Compact Omnidirectional Circularly Polarized Antenna via Alford Loop and Wire-Patch Structure Combination - Francesco Positano; Luca Santamaria; Robert Staraj; Leonardo Lizzi (IEEE Open Journal of Antennas and Propagation, 2024)
A compact single-fed omnidirectional circularly polarized (OCP) antenna is presented. The circular polarization is obtained by combining an Alford Loop (AL) and a Wire-Patch (WP) radiating structures, which are used to generate two orthogonal E-field components. The antenna exhibits a clear right-handed circular polarization (RHCP) with a dipole-like omnidirectional radiation pattern. A prototype has been realized using two FR-4 printed circuit boards (PCBs) and experimentally tested. The measured overlapped −10 dB impedance matching and 3 dB axial ratio bandwidth is 120 MHz wide (4.9%) from 2.40 to 2.52 GHz. The measured RCHP maximum realized gain and total efficiency are 1.91 dBic and 87%, respectively. Its compact size $(0.25λ × 0.25λ × 0.08λ)$ , and its low-cost, robust, and easy-to-realize structure make this antenna suitable for IoT applications.